Performance of Buffalo Calves as Influenced by Inclusion of Formaldehyde Treated Mustard Oil Cake in the Ration - Kumar, Pramod; Kumar, Sanjay; ., Chandramoni; Kumar, Kaushalendra; Singh, P.K.; Kumari, Jyoti; Sinha, Pallavi (Indian Journal of Animal Nutrition, 2018)
This study was conducted to know the effect of formaldehyde treated mustard oilcake on nutrient utilization, growth performance and economics of feeding in buffalo calves. Twelve Murrah buffalo calves (4 to 6 months old) were divided into two equal groups on the basis of their body weight. The ration offered to the animals of both the groups was same except that the untreated mustard cake used in the control group was replaced with formaldehyde treated (@ 1.2 g/100 g CP) mustard cake in the experimental group. DM intake was comparable in both the groups. The daily body weight gain was higher in formaldehyde treated group as compared to control group. The DCP content in the rations of treatment group was higher (P